Introduction of Stylos in Marvel Grass Stands - Harsh, L N; Mauria, S (Annals of Arid Zone, 2016)
Studies were carried out on the introduction ef stylos (Stylosanthes hamata (Linn.) Taub. and S. scabra) in Marvel grass (Dichanthium annualatum (Forsk.) Stapf) grassland with and without soil working. The maximum dry forage yield (42 q/ha) of grass legume mixture was recorded in treatment T3 (hamata plus D. annulatum with soil working). The crude protein yield was also highest (2.37 q/ha) in this treatment. Increase in the protein yield was over 88 09 percent as compared to the pure grass.